Transformasi Kemampuan MRO (Maintenance, Repair, and Overhaul) Satuan Perhubungan dalam Mendukung Tugas Pokok TNI AD - Pribadi, Adi Wahyu; Prihartoro, Mitro; Hipdizah, Hipdizah (Innovative: Journal Of Social Science Research, 2025)
Electronic communication devices in the military environment are currently developing with DSD technology so that in its maintenance, the MRO capability of Bengpushub Pushubad is required to follow DSD technology. In reality, the MRO capability at Bengpushub Pushubad is still focused on the maintenance of analog Alkomlek, thus creating a gap in maintenance capability, which can hamper operational readiness. The constraints that occur are due to the lack of personnel and the limitations of workshop facilities and infrastructure that are not yet modern and are still based on old technology. So it is necessary to analyze in carrying out transformation in the organizational, personnel and infrastructure aspects at Bengpushub in order to increase the effectiveness and efficiency of the MRO capability of Alkomlek which is the purpose of this study. For this purpose, this study uses a descriptive qualitative method with data obtained through in-depth interviews with related personnel, direct observation of the work process, and relevant literature studies. The results of the study require adjustments to the organizational structure in the Communication Unit in order to adapt to the demands of increasingly complex and dynamic MRO tasks. The quality of personnel is developed through new skills training in operating and maintaining DSD (Digital and Software Defined) technology equipment, while the existing workshop equipment facilities need to be equipped to create a supportive work environment. The conclusion of this study is from the organizational aspect through the validation of the Communication Unit Workshop organization that accommodates and adopts Alkomlek with Digital and Software Defined (DSD) technology, from the Personnel Aspect through Education and training in the use of Digital and Software Defined (DSD) technology in its maintenance and repair activities and from the Aspect of facilities and infrastructure through upgrading analog Alkomlek to Digital and Software Defined (DSD) technology tools to answer the needs and developments of the strategic environment faced.